Synthesis and evaluation of 2, 9-disubstituted-1, 10-phenanthroline derivatives as G-quadruplex binders. (1st November 2022) - Figueiredo, Joana; Carreira-Barral, Israel; Quesada, Roberto; Mergny, Jean-Louis; Cruz, Carla
Graphical abstract: Abstract: G-quadruplex (G4) structures are non-canonical DNA/RNA secondary structures able to form within guanine rich nucleic acids sequences. They are present in several regions of the human genome including gene promoters, untranslated sequences, and telomeres. Due to their biological relevance G4 structures are considered important drug targets, in particular for anticancer therapies, leading to the development of G4 stabilizing small molecules. Telomeric regions have received special attention in this field since they can fold into several distinct intramolecular G-quadruplexes topologies. Herein, we report the synthesis of 2, 9-disubstituted-1, 10-phenanthroline derivatives and their ability to stabilize different intramolecular telomeric G4 sequences. We evaluated ligand-induced stabilization, selectivity and specificity of ligands using Förster Resonance Energy Transfer (FRET) melting experiments and circular dichroism (CD). In addition, we assessed the cytotoxicity of ligands against two cancer cell lines (A549 and H1299) and one healthy cell line (NHDF).